SOUDAN DU SUD FACE À LA GUERRE CIVILE : Recomposition géopolitique du théâtre des rivalités des puissances - Agenonga Chober; Bahinduka Besisa (IJRDO - Journal of Social Science and Humanities Research, 2019)
The toppling over of South Sudan in a spiral of violence raised the veil on the rivalries of interests of the regional and extra regional powers. This episode entailed the slip of the theater of the conflicts of the region of the Great Lakes toward this part of Africa. From then on, the only geographical proximity appears shaky to the researcher to give account of the complexity of stakes that yet underlies the wild mobilization of some powers eccentric to this young State. From where the raise of debate on the regional dynamics. - Why did the South Sudan become a theater of rivalries of the foreign powers? - What means do these protagonists have to reach their objectives? - What are the consequences who ensue some? These are there the preoccupations that this note tempts to review with the fine-toothed comb.